The measurement model of historical awareness - Aisiah, Aisiah; Suhartono, Suhartono; Sumarno, Sumarno (REID (Research and Evaluation in Education), 2016)
The study aimed to develop a measurement model of historical awareness through a research and development model adopted from the Plomp model. Historical awareness was measured through four components, namely: knowledge of historical events, understanding of historical research method, meaning of historical events, and usefulness of history. The development procedures of the development model included a preliminary investigation in the form of literary study about the constructs of historical awareness. In the design stage, the researcher designed a conceptual model and a hypothetical measurement model about historical awareness. Then, the researcher performed a test construction namely assembling the test instrument for measuring historical awareness. Eventually, the researcher administered a test, did evaluation and made revision. The test in the study referred to the empirical testing of the instrument, while the evaluation in the study referred to the efforts to identify the obstacles that the participants encountered within the empirical testing of the instrument in order to revise it. The empirical testing of the instrument involved history teacher-candidates at Universitas Negeri Yogyakarta and Universitas Negeri Padang. The data were gathered through the test by using the measurement instrument in the form of associative multiple choice test. For the construct analysis, the researcher implemented confirmatory factor analysis by means of Lisrel 8.80 program. The results of the analysis show that the Ï‡2 = 121.98, the p-value = 0.11, RMSEA = 0.043. In other words, the measurement model of historical awareness that had been developed was supported by the empirical data.